NFC based attendance: more than just a touch - Zuhedy Zay, Aqqiela Zuhra; Mohd. Nor, Rizal; Mohamed Razi, Mohamed Jalaldeen; Mantoro, Teddy; Ayu, Media Anugerah (2015)
Current research shows that computer games were integral to the life of young learners across the globe. Hence, educators were looking at opportunities to use computer games in teaching and learning in order to address the needs of young learners. Meanwhile, learning needs and expectations were varied depending on the culture of a particular individual. Researches show that there were compelling connections between culture and learning, however studies in this area is still lacking. Thus, to address this limitation, four existing serious game models and frameworks were investigated. The outcome of this work is a serious game design model for culturally-enhanced serious game called GADEM. This model was extended from Four Dimensional Framework (FDF) and used pedagogical, Intercultural Communication and Social Construction of Technology (SCOT) as basis of extension. The target users of GADEM were both serious game designers and developers in order to guide them to design an effective serious game for learners.